Investigating the service brand: A customer value perspective - Leyla Heydari; Fereshteh Lotfizadeh (Management Science Letters)
This paper examines the effect of the service brand on the customer value–loyalty process. The study includes the traditional effect of brand image plus three additional influences, which reflects the broader service perspective including company image, employee trust, and company trust. Using survey data of a sample of 385 bank customers, the analysis indicates there is a direct influence of some of the perspectives of the brand on customers' perceptions of value. The results indicate that brand image, organization image, trust to firm influence positively on quality of services. In addition, brand image, organization image, quality of services and trust to firm influence on customer’s perspective where quality of services maintains the lowest impact and corporate image has the highest impact on customer’s perspective.